"Returning to Saussure" – Young Ho Shi - elmellakh, mhammed (El Omda in Linguistics and Discourse Analysis, 2018)
In this article ; Yong Ho Choi introduces some of the key entry points for re-reading saussure, and from there justifying this return. The main reasons are determined by the following elements – renewing the debate on saussure in the international scientific forum – the saussurean is not merely a historical fact that can be overcome. We are still under the influence of the saussurean linguistics because the problematic nature of its questions is still going on, and because we have not exhausted the potentials of saussurean thought. The image used in saussurean linguistics suggests othewise. In this article ; Yong Ho Choi invokes ideas of the pioneers of linguistic thought that tried to make saussure actual to us from different angles, the philological angle that separate saussure lessons from saussure manuscripts ; and the second angle , determined by the hermeneutic view which is based in the interpretation of the saussurean thought, by invoking the sociological and the historical factor. The author conclude with a very important conclusion, which is summed up in the following thesis ; returning to saussure does not mean returning to some historical origin , but returning to the source of the experiment where its potentials and issues are determined